Looking through a glass Bible : postdisciplinary Biblical interpretations from the Glasgow School - Adam, A. K. M. 1957- (Biblical Interpretation Series, 2013)
Some biblical interpreters' imaginations extend only as far as outlandish source theories or esoteric hypothetical audiences. The interpretive energies let loose in Glasgow over the past decade or so, however, have produced a cadre of interpreters who defy the disciplinary mandates of biblical criticisms in favour of reading the Bible with imaginations both careful and carefree. Infused with literary, political, art-critical, cinematic, liturgical and other interests, these essays display interpretive verve freed from the anxiety of disciplines - with closely observed insights, critical engagement with biblical texts, and vivid inspiration from the cultural world within which they are set. Here there is no \'gap\' between world and text, but the intimate congeniality of close, dear, comfortable interpretive friends. Contributors: Ben Morse, Hugh Pyper, Alastair Hunter, Hannah Strømmen, Jonathan C. P. Birch, Anna Fisk, Kuloba Wabyanga Robert, Samuel Tongue, A. K. M. Adam, Abigail Pelham, and the Religarts Collective (with Yvonne Sherwood).